Effects of ABCG2 421C > A genetic polymorphism on the pharmacokinetics of rivaroxaban in healthy Chinese subjects - Guo, Lingfang; Sun, Xue; Bo, Qiu; Bai, Wanjun; Du, Yabin; Song, Haojing (Xenobiotica, 2025)
The main objective of this study is to investigate whether the CYP3A4/5 and ABC transporter genetic polymorphisms could affect the pharmacokinetics (PK) of rivaroxaban in Chinese healthy subjects.Forty-two healthy subjects in China were recruited and given a single dose of 2.5 mg rivaroxaban tablets. Plasma concentration of rivaroxaban was determined by UPLC-MS/MS, the CYP3A4 20230 G > A(*1G)), CYP3A5 6986 A > G(*3), ABCB1 1236 C > T, ABCB1 3435 C > T, ABCB1 2677 G > T/A, ABCG2 34 G > A, ABCC2 1249 G > A, ABCC2 3972 C > T, ABCC2 - 24 C > T, ABCG2 421 C > A, SLC22A8 715 C > T, SLC22A8 445 C > A, SLC22A8 779 T > G, SLC22A8 829 C > T, and SLC22A8 913 A > T genotypes were determined by SnapShot Technique.In the study, compared with the subjects with C/C of ABCG2 421 C > A genotype, individuals with C/A and A/A genotype showed higher the area under the concentration-time curve AUC (289.17 358.56 439.26 ng/h/mL) ( < 0.05 and < 0.01, respectively), AUC (293.92 362.80 442.25 ng/h/mL) ( < 0.05 and < 0.01, respectively) and the maximum plasma concentration (56.58 70.36 83.90 ng/mL) ( < 0.05 and < 0.01, respectively), but lower apparent clearance CL/F (9114.00 7493.82 6017.75 mL/h) ( < 0.05). Following Bonferroni correction, subjects carrying the A/A genotype continued to exhibit statistically significant differences in PK parameters , AUC , and AUC compared to C/C allele carriers.Data in the article proved that the ABCG2 421 C > A polymorphism was significantly related to the PK variability of rivaroxaban.